QUESTIONS AND INSTRUCTIONS DELIVERED BY SENIOR AND JUNIOR ENGLISH TEACHERS AT A PRIVATE SENIOR HIGH SCHOOL IN SIDOARJO - Bobby W Setiawan; Esther H Kuntjara (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
This study is related to a study of classroom discourse about delivering questions and instructions based on the cognitive domains done by senior and junior English teachers in secondary level. The study was conducted in the first grade of Senior High School which was facilitated by different English teacher,  It was revealed that all the questions and instructions delivered by both English teachers were mostly applied in the lowest level of cognitive domain (‘remembering’ and ‘understanding’) because those teachers considered the level of students because in this level, the first grade students were still needed to retrieve their memory, knowledge, and understanding of what they learned during the class time. However, those two teachers were still applied another domain. The number of cognitive domains applied were different. The senior teacher applied five of six cognitive domains while the junior teacher only applied four of six cognitive domains